"My Life Belongs to Me": Exemplifications of Personal Agency in the Lives of Two African Refugees in Sicily. (December 2015) - Reale, Michelle
There is an interesting dynamic whenever I, the researcher, approach a refugee to interview. Often I meet the refugee when he is in a state of shock or high agitation, as many are upon their arrival in the refugee camps. Showing some resistance to questioning can be seen as a good sign, as the refugee begins to show some discernment toward to whom he will tell his story with an understanding that he is under no obligation to do so. This is in contrast to those who are very compliant, often telling a similar tale to so many others, something that I call the "voyage story, " a narrative that speaks of the physical trials of passage, but usually none of the feelings or emotions that go with them. In the poems that follow, two refugees exemplify personal agency, though in different ways.